“Harmoni” dalam profesionalisme sebagai pustakawan tunggal: Studi kasus Perpustakaan Teknik Pertambangan Institut Teknologi Bandung - Resti Andriani (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2017)
One Person Librarian is a librarian who manages libraries in an institution / institution alone. This phenomenon has become increasingly common in libraries majoring in / faculty of universities apply this model. This can be due to a lack of professional librarians and cost efficiency. The author is a librarian who manages library majors alone, or often called One Person Librarian. Activities undertaken are collection development, library material processing, service and other library administration activities. In the course of time must sometimes feel saturated, but must always be remembered the motto of ITB is